Grinding of cemented carbide using a vitrified diamond pin and lubricated liquid carbon dioxide - Kareepadath Santhos, Deepa (Strojniški vestnik, 2023)
Despite extensive research on grinding of cemented carbide, few studies have examined abrasive machining of this material using small-diameter super abrasive tools (also known as grinding pins/points), especially with respect to varying cooling-lubrication methods. This study therefore focuses on a comparative experimental investigation of three such methods - dry, emulsion, and lubricated liquid carbon dioxide (LCO2-MQL). The performance of these methods and the resulting grindability are examined in terms of grinding forces, force ratios, specific energy, and through the analysis of wheel loading. The results show that LCO2-MQL grinding has lower grinding forces (normal forces – 8 % to 145 % lower than dry grinding, and 18 % to 33 % lower than emulsion grinding and tangential forces – 4 % to 66 % lower than dry grinding and 28 % to 78 % lower than emulsion grinding) and specific energy 24 % to 51 % lower compared to dry grinding and 64 % to 69 % lower than emulsion grinding, indicating its potential for efficient material removal. However, a challenge with high wheel loading was observed with LCO2-MQL, likely due to the lack of oxygen in the CO2 grinding atmosphere. Despite this issue, the LCO2-MQL method shows potential for efficient operations, especially at higher aggressiveness values where the lowest specific energies were achieved. These results provide new insights into various aspects of cooling-lubrication methods in the pin grinding of cemented carbides.
Keywords: brušenje; carbon dioxide; cemented carbides; cooling-lubrication; diamantni brus; diamond; enokanalni dovod; grinding; hlajenje; kapljeviti ogljikov dioksid (LCO2); karbidne trdine; mazanje; minimalna količina mazanja (MQL)